Strategi Kepala Sekolah Dalam Peningkatan Motivasi Dan Etos Kerja Guru Di Sekolah Menengah Atas Negeri Bareng Jombang - Noor Fatikah; Fildayanti (Indonesian Journal of Islamic Education Studies (IJIES), 2019)
As a motivator, headmasters should have a good strategy to motivate teachers in carrying out various tasks and functions. They have to have views and attitudes toward their employers. The headmaster of SMAN Bareng is one of the principals who always motivates his teacher. For examples, giving prizes in the form of awards and cash to outstanding teachers. This study is qualitative, data is collected through observation, documentation and interviews, and to analyze the researchers' data using triangulation of sources. The results of the research are: the teacher of SMAN Bareng have a very good motivation, in terms of self-esteem needs which include the need for achievement and the need for status, such as several teachers are taking master's programs. The work ethic possessed by SMAN Bareng teacher is very good, as that is they have the discipline of time and responsibility in carrying out the tasks given by the principal. The principal's strategy in increasing teacher motivation and work ethic is making a good plan and giving models to them.